Penerapan Logika Fuzzy Pada Rancang Bangun Alat Pakan Kucing Otomatis dan Monitoring Sisa Pakan Dengan Aplikasi Blynk - Khoiroh, Siti Husnul; Ridwan, Mohammad; Maftukhah, Siti (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
Keeping cats is one of the fun hobbies among the community, because cats are one of the cute animals and close to humans, besides that cats are able to reduce stress, anxiety and the risk of stroke. However, in the maintenance of cats must pay attention to diet and cleanliness so that cats are not susceptible to disease. Internet of Things (IOT)-based cat feeding device is a tool that serves to feed cats remotely using the web, many of them are cat keepers who are constrained in feeding because they are busy with their respective activities. This tool is expected to make it easier for cat owners who find it difficult to feed their cats, this tool can work automatically using the RTC module for timing of feeding and can also control via a smartphone web when adding portions, this tool can also add monitoring portions The rest of the feed in the container uses a Load cell, and takes a picture of the cat's condition with the camera then the image results and the rest of the feed will be sent to the web.